Pengaruh Penggunaan Model Pembelajaran Children Learning In Science (CLIS) Terhadap Hasil Belajar Fisika Siswa Kelas VII SMP Negeri 7 Ternate - Siti Nahria Hasan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to find out: (1) the implementation of the Children Learning In Science learning model for class VII students of SMP Negeri 7 Ternate on temperature, (2) the results of learning physics for class VII students of SMP Negeri 7 Ternate. using the Children Learning In Science learning model; and (3) the effect of using the Children Learning In Science (CLIS) Learning Model on the Physics Learning Outcomes of Class VII Students of SMP Negeri 7 Ternate on Temperature Material. Tests of student learning outcomes and observation tables of learning and educational activities are used as aids in this research. Inferential descriptive statistical data analysis and t-test were used as data analysis techniques. The results of this study indicate that: (1) Observation table of analysis of teacher learning activities on the application of Children Learning In Science learning in class VII students of SMP Negeri 7 Ternate in the subject of temperature is in the very high category; (2) The test results of class VII students of SMP Negeri 7 Ternate on temperature material taught using the Children's Learning In Science learning model used in this study can improve student learning outcomes and are in the high category; (3) the children's science learning model is very effective in improving the learning outcomes of class VII students of SMP Negeri 7 Ternate in the subject of temperature. The conclusion in the research is that because the Children Learning In Science learning model can improve high learning outcomes, it is hoped that researchers/teachers will then conduct further research using the Children Learning In Science learning model according to the material to be taught